Uporaba tuje znamke po noveli ZIL-1E - Robnik, Thomas (Podjetje in delo, 2021)
The article examines the fundamental limitations of trademark rights under Article 48 of the Industrial Property Act. Following the entry into force of the Act Amending the Industrial Property Act (ZIL-1E), this article underwent significant changes as part of a comprehensive reform of trademark law. The amendments relate in particular to the scope of individual provisions (the use of name or address is now restricted to natural persons, descriptive use is extended to the use of non-distinctive signs or indications), and two new restrictions have been added (referential use and use of an earlier right, which only applies in a particular locality). It is noted that the revision of the provisions was in principle welcome and appropriate, and the Act Amending the Industrial Property Act (ZIL-1E) consistently followed Directive 2015/2436; however, certain ambiguities are highlighted, especially in the light of the interpretation of certain provisions.
Keywords: company name; dobri poslovni običaji; earlier rights; firma; honest practices; limitations of trademark rights; omejitve pravic iz znamke; osebno ime; personal name; prejšnje pravice; trademark; znamke